PEMBELAJARAN MODEL CIRCUIT TRAINING UNTUK MENINGKATKAN KOMPETENSI GRAMATIKAL-LEKSIKAL MAHASISWA BAHASA JERMAN - Rosyidah Rosyidah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
This article  reports  on   a research    aimed  at improving  the students’ grammatical-lexical competence using learning  model circuit training. The subjects were the students  of the German Department who took part in the lecture Struktur und Wortschatz 1 Off  AA in 2009.  The results show that  the process consists of four main phases: motivation, going around, training,   and presenting; and  the ac- tions had  the effects: all students were totally active and75 % of  the students  could present  the learning  materials  correctly,  the average  point at the end of the second cycle (70,58) can be regarded as successful